2015
DOI: 10.5398/medpet.2015.38.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Blood Malondialdehyde, Reproductive, and Lactation Performances of Ewes Fed High PUFA Rations Supplemented with Different Antioxidant Sources

Abstract: The aims of this study were to evaluate the effect of vitamin E (vit E) and black tea extract (BTE) as antioxidant sources in high poly-unsaturated fatty acid (PUFA) rations on blood malondialdehyde (MDA) concentrations and the performance of reproduction and lactation of Garut ewes. Twelve ewes on late pregnancy periods were divided into completely randomized design (CRD) with 3 treatments and 4 replicates. The treatments were control: basal diet without antioxidant, vit E: basal diet supplemented with vit E,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
6
1
Order By: Relevance
“…The lowest ADG in P3 is likely related to tendency for birth weight to be lighter than the other treatments. However, the result in ADG of single and twin type lambs in this study was higher than the result reported 141 g/head/day in a single type and 84 g/head/day in twin type (Fassah et al, 2015), or in the single kid is 120 g/head/day (Astuti et al, 2019).…”
Section: Lamb Performancecontrasting
confidence: 87%
“…The lowest ADG in P3 is likely related to tendency for birth weight to be lighter than the other treatments. However, the result in ADG of single and twin type lambs in this study was higher than the result reported 141 g/head/day in a single type and 84 g/head/day in twin type (Fassah et al, 2015), or in the single kid is 120 g/head/day (Astuti et al, 2019).…”
Section: Lamb Performancecontrasting
confidence: 87%
“…According to Noeman et al (2011), a high-fat diet reduced the activity of antioxidant enzymes (SOD, GPx) in rats, whereas MDA levels were higher, indicating oxidative stress. Additionally, in a study on sheep, intensified lipid peroxidation was detected perinatally as an effect of higher dietary supply of PUFA (Fassah et al, 2015). Total of C20: 5n -3, C22: 5n -3, and C22: 6n -3.…”
Section: Discussionmentioning
confidence: 97%
“…Fassah et al . [ 4 ] mentioned that the high metabolic demand in lactation and late pregnancy period also induced oxidative stress.…”
Section: Introductionmentioning
confidence: 99%